Analisis Penerapan Pajak Pertambahan Nilai (PPN) Pada PT. Wira Kusuma - Andi Lutfi; Faisal; Basar, Nur Fatwa (STIM-LPI Makassar, 2024)
This research aims to determine the application of Value Added Tax at PT. Wira Kusuma based on Law no. 42 of 2009 concerning applicable tax regulations. The data analysis method in this research uses descriptive analysis. The types of data used are qualitative data and quantitative data, this research uses primary data sources and secondary data. The results of this research indicate that the application of Value Added Tax at PT. Wira Kusuma has implemented it in accordance with the implementation of Value Added Tax in Law no. 42 of 2009 and tax regulations, thus the proposed hypothesis is rejected.